Pembaruan Pemahaman Bahasa Hukum Indonesia Dalam Penafsiran Konstitusi Untuk Jaminan Kepastian Hukum - Elnizar, Normand Edwin (Jurnal Hukum & Pembangunan, 2022)
This article attempts to explain legal language aspects need to be improved in implementing laws that uphold justice while at the same time provide legal certainty. The study is limited to the constitution as the highest law in the national legal system. The explanation of the linguistic aspect including foreign legal terminology in the constitutional interpretation and the constitutional interpretation as a discourse analysis. It was conducted by literature research to compare the paradigm of constitutional interpretation theory with linguistic aspects in linguistic theory. Decision Number 84/PUU-XVI/2018 used as example for this research. This qualitative research describes some linguistic aspects are useful for legal certainty in implementing laws. The main goal is upholding justice while at the same time ensuring better legal certainty. Constitutional interpretation theory and theories in linguistics are described to capture problems that occur regarding legal certainty. The linguistic theory described are register from sociolinguistic, semantic, and discourse theory. The results of this study indicate that the interpretation of the constitution in Decision Number 84/PUU-XVI/2018 has made good use of the understanding in semantic studies for the use of foreign legal terminology. The results of this study also assess that the use of discourse theory can combine the results of the interpretation of originalism and non-originalism as a unitary meaning of the constitution. This method can be useful in increasing legal certainty by combining results from the interpretation of originalism and non-originalism.